Evidence of physiological changes associated with single-session pre-frontal tDCS: a pilot study - Rembrandt, Hannah N.; Riley, Ellyn A. (Frontiers in Human Neuroscience, 2025)
ObjectiveTranscranial direct current stimulation (tDCS), a non-invasive, painless method of applying direct current electrical stimulation to specific areas of the brain, is an effective method for enhancing attention and post-stroke fatigue, as shown by behavioral improvements in post-stroke populations. While behavioral evidence supports this method, there is a paucity of physiological data corroboration of this improvement. The current study is designed to investigate if a single session of tDCS will improve attention and fatigue as shown by relevant physiological methods in persons with post-stroke aphasia.MethodsTen participants (5 male; mean age: 62.8) engaged in two identically structured data collection sessions with at least a 3-day wash-out period between them. Sessions started with a sustained attention task with simultaneous electroencephalography (EEG) and pupillometry data collection, followed by an attention training program with simultaneous active or sham tDCS. Following tDCS, participants repeated the sustained attention task with simultaneous EEG and pupillometry data collection. Participants received active tDCS during one session, and sham tDCS during the other, with the order randomized.ResultsNo differences between conditions were found for either behavioral results from the sustained attention task (i.e., reaction time of correct responses; n = 9 p = 0.39) or EEG measured attention state data for any of the four attention states: no attention (n = 10, p = 0.83), distracted attention (n = 10, p = 0.20), moderate attention (n = 10, p = 0.95), or high attention (n = 10, p = 0.62). Pupil dilation was significantly greater in the post-active tDCS stimulation condition than in either pre-training condition (n = 10, p < 0.01). tDCS stimulation lessened the increase in task-based fatigue from the beginning to the end of the session such that there was a significant increase in task-based fatigue when participants received sham tDCS (n = 10, p = 0.01) but no significant change in task-based fatigue during the active condition session (n = 10, p = 0.12).ConclusionChanges in pupil diameter observed in the active stimulation condition suggest activation of the locus coeruleus-norepinephrine (LC-NE) pathway within a single session of tDCS administration, but the lack of significant changes for either response time or attention states indicate no direct effect on behaviorally measured or EEG measured attention within the same timeframe. Responses to active stimulation in terms of subjective fatigue rating varied between individual participants; overall, active tDCS mitigated task-based fatigue. More research is needed to investigate this relationship.